2019
DOI: 10.33594/000000072
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine Accelerates Cystic Kidney Disease in a Pkd1-Deficient Mouse Model

Abstract: This article is licensed under the Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International License (CC BY-NC-ND). Usage and distribution for commercial purposes as well as any distribution of modified material requires written permission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 57 publications
1
12
0
2
Order By: Relevance
“…Hypertension, which occurs prior to loss of kidney function in 60% of ADPKD patients, represents a significant independent risk factor for progression of the disease, contributing to cyst expansion and intrarenal ischemia hence activating intrarenal renin-angiotensin-system (RAS) (46). Besides genetic factors, predictors that may lead to cyst growth and increase in TKV in ADPKD also include male gender, high salt and protein intake, caffeine consumption, level of fluid intake, gross hematuria, nephrolithiasis, proteinuria among others (713). Inflammation, present even in initial stages of the disease may also influence the progression of ADPKD (14).…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension, which occurs prior to loss of kidney function in 60% of ADPKD patients, represents a significant independent risk factor for progression of the disease, contributing to cyst expansion and intrarenal ischemia hence activating intrarenal renin-angiotensin-system (RAS) (46). Besides genetic factors, predictors that may lead to cyst growth and increase in TKV in ADPKD also include male gender, high salt and protein intake, caffeine consumption, level of fluid intake, gross hematuria, nephrolithiasis, proteinuria among others (713). Inflammation, present even in initial stages of the disease may also influence the progression of ADPKD (14).…”
Section: Introductionmentioning
confidence: 99%
“…A recent report, on the other hand, found that smoking status did not influence renal survival in this disease 11 . Similarly, in vitro and in vivo experimental data suggested a detrimental effect for caffeine 12 , 13 , which was not confirmed by recent clinical studies 14 , 15 .…”
Section: Introductionmentioning
confidence: 72%
“…Quando se trata de investigar as atitudes políticas enquanto essas se expressam no campo da linguagem, emerge, na literatura, a noção de ideologia (Singer 1999 De outro lado, compreendem-se as ideologias políticas como "sinalizadoras de orientações" (Singer 1999, 35), quer dizer, como signos sintéticos que permitiriam às pessoas em geral mapearem o cenário político, mesmo sem terem desse uma compreensão clara e circunstanciada.…”
Section: Atitudes Políticas E Plano Discursivounclassified
“…No Brasil, Singer (1999), alinhado à segunda perspectiva, argumenta que a ideologia cumpre um papel central na definição das atitudes políticas. Já os estudos que se alinham à primeira perspectiva, tendem a mostrar o contrário.…”
Section: Atitudes Políticas E Plano Discursivounclassified